2017
DOI: 10.1080/13625187.2017.1409346
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Revised Impact of Miscarriage Scale for Swedish conditions and comparison between Swedish and American couples’ experiences after miscarriage

Abstract: The high consistency between the countries suggests that the RIMS questionnaire is reliable for both women and men to be used in both countries and two of three factors were similar between the two countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…A strength of the study is that the cultural origin of the women is the same as would be expected in the general population, and we assume that the results are valid for Swedish conditions. This is in line with our previous study, where we show that experiences of miscarriage are the same regardless of cultural differences …”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…A strength of the study is that the cultural origin of the women is the same as would be expected in the general population, and we assume that the results are valid for Swedish conditions. This is in line with our previous study, where we show that experiences of miscarriage are the same regardless of cultural differences …”
Section: Discussionsupporting
confidence: 94%
“…This contrasts with a previous study, where there were no differences in any of the RIMS factors after 4 months, and it was speculated that longer time was needed to recover from a miscarriage. The reason for the discrepancy could be cultural differences, despite our previous study showing that the experiences after miscarriage were similar in Swedish and American couples after 1 week, but comparisons on the longitudinal level were lacking …”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Qualitative studies were generally of a high standard, with methodologies and analyses (content [46,55,60,64,69], thematic [61,65,71,72], grounded theory [59,62,68], autoethnographic [66], descriptive [83] and phenomenological [56-58, 73-75, 77-82]) clearly reported and justified in the context of 'exploratory' or 'understanding lived experience' research aims. Quantitative studies reported either correlational and regression analyses [24,67,76,86,88,90,92,93], or group difference tests [23,25,76,84,87,89,91,[94][95][96], including significance testing of resulting relationships or differences. However, one small quantitative study reported only numbers and percentages of participants who endorsed a particular feeling relating to grief or service outcome [70], and another reported percentages of participants who had received certain support services following a loss [95].…”
Section: Quality Of Included Studiesmentioning
confidence: 99%